Penerapan Terapi Komplementer POMMEL (Pijat Oksitosin Menggunakan Minyak Esensial Lavender) Untuk Meningkatkan Produks Asi Pada Ibu Nifas - Yanti, Ariu Dewi (Universitas Pahlawan Tuanku Tambusai, 2025)
Breast milk (ASI) is an important nutrient for babies, especially in the first month of life. In Indonesia, exclusive breastfeeding is still below the expected target. One of the reasons for the failure to achieve exclusive breastfeeding is because the milk production is not smooth in the early postpartum period. One way to overcome the problem of breast milk production is to carry out complementary POMMEL therapy (Oxytocin Massage Using Lavender Essential Oil). This study aims to determine the application of complementary POMMEL therapy (Oxytocin Massage Using Lavender Essential Oil) to increase breast milk production in postpartum mothers. The type of research used is Pre-Post one group design. The research design carried out two tests, namely before and after being treated. The sample technique used was total sampling with a total of 20 respondents. The research instrument used an observation sheet and a questionnaire. The results of the study were interpreted as a percentage and the data results were presented in the form of a Crosstab. The results of the study were obtained from 20 respondents, before the implementation of complementary therapy POMMEL, most of them, namely 16 respondents (80%) experienced irregular breast milk production, after the implementation of complementary therapy POMMEL, almost all of them, namely 19 respondents (95%), had smooth breast milk production. Complementary therapy is one of the right solutions to overcome problems that are often experienced during the postpartum period and complementary therapy can be applied to postpartum mothers, one of the benefits of which is to increase breast milk production.